In Silico Optimisation Of Domain Antibodies Against HSP16.3 From Mycobacterium Tuberculosis - Soong, Jia Xin (2018)
Heat shock protein 16.3 (HSP16.3) from Mycobacterium tuberculosis (Mtb) is critical for its survival during latent infection in human, thus making it an attractive target for developing diagnostic and therapeutic strategies. The predicted structure of HSP16.3 was docked against a known HSP hydrophobic probe, namely 4,4′-dianilino-1,1′-binaphthyl-5,5′-disulfonic acid (bisANS) and to the comparative models of HSP16.3 specific single domain antibodies (sdAbs), clone E3 and F1. The binding interactions were further elucidated by free energy calculations. The non-polar interactions were identified as the main force for antigen-antibody association.